PERSEPSI ORANG TUA TENTANG KEKERASAN VERBAL PADA ANAK - Annora Mentari Putri; Agus Santoso (Jurnal Keperawatan Diponegoro, 2012)
Verbal abuse which doesn’t give less bad impact compare with physical abuse. Parent indicated that abuse on children is only physical abuse just like hitting, tweaking ear and throwing objects. In fact physical abuse is almost always accompanied by verbal abuse such as snapping, shouting at and child neglect. The purpose of this research is to know parents perceptions about verbal abuse that is done on children. This research uses qualitative method of phenomenological approach. The population in this study was parents who had children ages 3 to 6 years lived in Kebondalem district Kendal. Sample done purposively. The participants are 4 people who has minimum bachelor degree education and has the number of children not more than two children. Data collection techniques with in-depth interviews. This research resulted 4 themes shape from 6 subthemes, 14 categories, 66 core categories and 221 keywords. Two of four participants said verbal abuse is verbal words which should not proper be spoken. All participants understood that verbal action can be verbally abusive behavior. Parent are still doing verbal abuse on a child eventhough they understand about the verbal abuse. Parents argue that impact of verbal abuse is not too serious if compare to physical abuse